READABILITY LEVEL OF â€œBAHASA INGGRISâ€ TEXTBOOK FOR THE SEVENTH GRADE STUDENTS - Fahriah, Fahriah; Rahayu, Puji Sri (English Department of Faculty of Tarbiyah and Teacher Training, 2015)
This research aims to investigate the level of readability of ?Bahasa Inggris? textbook for the seventh grade students published by Mediatama and to know whether ?Bahasa Inggris? textbook is readable for the seventh grade students. The population of this study is + 210 students of seventh grade of SMP Negeri 1 Banjarmasin. The sample is 20% of the population or 42 students. The sample is chosen by using random-sampling techniques which is taken 6 students in each class. To collect the data, the writer uses two techniques that are cloze test and readability formula (Flesch Reading Ease Formula). The result of this research showed that through Flesch Reading Ease Formula, the readability score for the whole texts of the English textbook entitled ?Bahasa Inggris? is 76,35 (fairly easy) and through cloze test, the textbook has high readability which shown by its readability score 62,068. It means that ?Bahasa Inggris? Textbook Published by medaiatama is readable and suitable for the seventh grade of SMP Negeri 1 Banjarmasin.